Dermoscopy in Pediatric Dermatology – Part I: Skin Tumors - Pimenta, Rita (2020)
Melanocytic lesions and other skin tumors represent one of the most frequent reasons for pediatric dermatology consultation. Although often benign, some of them may simulate melanoma, which can be a source of anxiety for parents and clinicians. Dermoscopy is a non-invasive and painless technique that increases the diagnostic accuracy for skin tumours, while avoiding unnecessary skin biopsies. In part I of this article, we highlight the importance of dermoscopy for the diagnosis of skin tumors in pediatric patients.